大型能源装置行星齿轮传动模糊可靠性研究 - 尚珍; 王长明; 刘忠明 (Jixie chuandong)
According to the theory of fuzzy reliability analysis,the reliability model is developed for contact strength of tooth surface and bending strength of tooth root of planetary gear transmission.The effects of the center distance, the module and the limit stress of contact strength and bending strength are studied through some examples.At the same time,based on a large number of calculated data,the relationship between fuzzy reliability level and safety factor is analyzed.